2022
DOI: 10.1021/acs.orglett.2c02693
|View full text |Cite
|
Sign up to set email alerts
|

Sequential One-Pot Carbene-Catalyzed Intramolecular Stetter Reaction and Acid-Mediated Condensation: Access to Heteroatom Analogues of π-Extended Polyaromatic Hydrocarbons

Abstract: In this Letter, we disclose a simple and effective method to access a variety of phenanthro[9,10-b]furan and 1Hdibenzo[e,g]indole derivatives based on the design of a carbenecatalyzed intramolecular Stetter reaction followed by a Paal−Knorr reaction in one-pot. These compounds are a class of π-extended polycyclic aromatic hydrocarbon (PAH) derivatives containing an oxygen/nitrogen atom. The practical utility of the developed transformation was demonstrated on the gram scales and postsynthetic transformations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Based on control experiments and literature precedence, , a plausible mechanism for an NHC-catalyzed tandem imine umpolung–intramolecular aza-Michael addition–oxidation for the synthesis of isoindolinone derivatives is depicted in Scheme . Initially, carbene I is generated by the action of the base on the NHC precatalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on control experiments and literature precedence, , a plausible mechanism for an NHC-catalyzed tandem imine umpolung–intramolecular aza-Michael addition–oxidation for the synthesis of isoindolinone derivatives is depicted in Scheme . Initially, carbene I is generated by the action of the base on the NHC precatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The Douthwaite and co-workers and Rovis and co-workers reported the isolation of the nitrogen analogue of a Breslow intermediate, known as an aza-Breslow intermediate, from a stoichiometric reaction of NHC and imines . Our group and Biju and co-workers, for the first time, developed NHC-catalyzed imine umpolung as a key step to access indoles. , Recently, the NHC-catalyzed umpolung of imines enabling various organic transformations was reported by our group and the research groups of Biju, Fu, Lupton, and Chi . Imines are important building blocks for the synthesis of amides and nitrogen heterocycles .…”
Section: Introductionmentioning
confidence: 86%
“…As part of our ongoing efforts in the synthesis of fused heterocycles/carbocycles using enones, [22] we designed a substrate 1 a, having activated and unactivated alkene moieties tethered to benzene ring; and planned to explore its reactivity in the presence of visible light photoredox catalysis. Initially, 1 a was irradiated with blue LEDs in the presence of photocatalyst Ru(bpy) 3 Cl 2 .6H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…There is a reasonable number of reports on the individual synthesis of phenanthrenes [16][17][18][19][20][21] and pyrazoles. [22][23][24][25][26] For instance, the research group of Wang demonstrated the efficient formation of phenanthrols starting from diphenyl dicarbonyls and tosyl hydrazide under basic conditions (Scheme 1a).…”
mentioning
confidence: 99%